Entrepreneurial and Market Orientation, Customer Relationship Management, Micro, Small, and Medium Enterprises Performance: Competitive Advantage, Technology Turbulence Effects - Rahmadi, Afif Nur; Sudarmiatin, Sudarmiatin; Soetjipto, Budi Eko; Churiyah, Madziatul; Putra, Yudiarto Perdana (International Review of Management and Marketing, 2026)
This study examines how entrepreneurial orientation, market orientation, and customer relationship management influence the business performance of local wisdom-based culinary micro, small, and medium enterprises, with competitive advantage as a mediating variable and technological turbulence as a moderating variable. A quantitative explanatory approach was used, based on survey data collected from 384 culinary enterprise owners and managers in the former Kediri Residency, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling to assess direct, indirect, and moderating effects among latent constructs. Entrepreneurial orientation and customer relationship management have a positive and significant effect on business performance, whereas market orientation does not have a direct effect. Competitive advantage significantly mediates the impact of entrepreneurial orientation and market orientation on performance, but does not mediate the relationship between customer relationship management and performance. Technological turbulence does not strengthen the effects of entrepreneurial orientation or market orientation on performance, but it weakens the impact of customer relationship management. The findings indicate that internal strategic capabilities are more critical drivers of performance than technological dynamics. Competitive advantage is a key mechanism by which strategic orientations are translated into sustainable business performance for local wisdom-based culinary enterprises. This study is novel in showing how competitive advantage mediates strategic orientations and how technological turbulence shapes MSME performance in local wisdom–based culinary enterprises.